A “leaky pipeline”?: Factors affecting the career development of senior-level female administrators in NCAA Division I athletic departments - Hancock, Meg G.; Hums, Mary A. (Sport management review, 2016)
•Women play a conscious and active role in shaping their careers.•Relationships and professional activities are vital components to career development.•Women pursue positions that align with their career interests, goals, and values.•Value congruence may perpetuate a male-dominated organizational structure. National governing bodies, international sport federations, and national Olympic committees continue to struggle to attain minimal levels of female representation. Sport organizations in the United States are no exception. Despite the fact that more women work in intercollegiate athletics than ever before, the number of female assistant and associate athletic directors is declining. As such, fewer women are in the “pipeline” to achieve the position of Athletic Director. The purpose of this study was to identify factors that may influence women's career development in intercollegiate athletic administration. Twenty assistant and associate athletic directors were interviewed about their career paths, experiences, and goals. Results suggest strong interpersonal relationships with supervisors and mentors and access to professional development activities aided in participants’ career advancement. Factors attributed to perceptions of gender and professional value incongruence affected women's career choices and opportunities for advancement. Theoretical and practical implications are also discussed.